2012
DOI: 10.1002/hep.24623
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gene Expression Involving Innate Immunity and Genetic Variation in Interleukin 28B With Antiviral Response

Abstract: Innate immunity plays an important role in host antiviral response to hepatitis C viral (HCV) infection. Recently, single nucleotide polymorphisms (SNPs) of IL28B and host response to peginterferon a (PEG-IFNa) and ribavirin (RBV) were shown to be strongly associated. We aimed to determine the gene expression involving innate immunity in IL28B genotypes and elucidate its relation to response to antiviral treatment. We genotyped IL28B SNPs (rs8099917 and rs12979860) in 88 chronic hepatitis C patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
3
46
1
Order By: Relevance
“…Unlike the IL28B SNP, rs12979860, which is associated with HCV clearance, there are few studies focusing on the mechanisms by which HLA gene variations may influence the development of HBV infection. Furthermore, studies investigating the mechanism between IL28B variation and HCV clearance have shown that IL28B variation is associated with other immune factors (19,21,29,30). Therefore, we attempted to define the association between genes of the innate immunity and HLA variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the IL28B SNP, rs12979860, which is associated with HCV clearance, there are few studies focusing on the mechanisms by which HLA gene variations may influence the development of HBV infection. Furthermore, studies investigating the mechanism between IL28B variation and HCV clearance have shown that IL28B variation is associated with other immune factors (19,21,29,30). Therefore, we attempted to define the association between genes of the innate immunity and HLA variation.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL28B rs12979860 is a good predictor for HCV clearance (16), the level of IFN lambda 3, coded for by the IL28B gene, does not crucially influence the outcome in HCV infection (16,17). However, abnormal innate immune responses such as high levels of IL-10 and low IL-12p40 were found in patients with the poor-response genotype (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Two major polymorphisms, rs12979860 (C>T) [76,77] and rs8099917 (T>G) [72,73], in strong linkage disequilibrium are associated with responses to PEG-IFN and RBV [71,78]. The mechanism might be related to the regulation of innate immune responses by the IL28B gene product, IFN-λ3 [79]. The association appears relatively weaker between IL28B genotype and simeprevir with PEG-IFN and RBV.…”
Section: Pharmacogenetics In the Treatment Of Hcv Infectionmentioning
confidence: 99%
“…One explanation for this is that patients with the unfavorable genotype exhibit continual, ineffectual intrahepatic expression of ISGs. At the same time, IFN-signaling inhibitors such as SOC3 and protein inhibitor of activated STAT 1 are also upregulated; this preactivated ISG response may be insufficient to clear the virus, but it may cause reduced sensitivity to PEG-IFN-α therapy through negative regulation of JAK-STAT signaling by IFN-signaling inhibitors [104,106]. Thus, even when PEG-IFN-α is administered, the cell may fail to induce strong enough ISG expression and be unable to clear the virus [106].…”
Section: Pharmacogenomicsmentioning
confidence: 99%